The novel peptide LCGM-10 attenuates metabotropic glutamate receptor 5 activity and demonstrates behavioral effects in animal models - Malyshev, Anton V.; Pavshintcev, Vsevolod V.; Mitkin, Nikita A.; Sukhanova, Iuliia A.; Gedzun, Vasilina R.; Zlobin, Alexander S.; Doronin, Igor I.; Babkin, Gennady A.; Sawyer, Tomi K. (Frontiers in Behavioral Neuroscience, 2024)
We employed a structural bioinformatics approach to develop novel peptides with predicted affinity to the binding site for negative allosteric modulators (NAMs) of metabotropic glutamate receptor 5 (mGluR5). Primary screening in zebrafish (Danio rerio) revealed a stimulatory effect of two peptides, LCGM-10 and LCGM-15. Target validation studies using calcium ion flux imaging and a luciferase reporter assay confirmed mGluR5 as the target. LCGM-10 showed greater potency than LCGM-15; it was comparable to that of the mGluR5 NAM 2-methyl-6-(phenylethynyl)pyridine (MPEP). Rodent behavioral screening in the open field and elevated plus maze revealed increased locomotor activity in both tests after acute LCGM-10 treatment, supported by further analysis of home cage spontaneous locomotor activity (SLA). The stimulating effect of a single LCGM-10 administration on SLA was evident up to 60 minutes after administration and was not accompanied by hypokinetic rebound observed for caffeine. According to our results, LCGM-10 has therapeutic potential to treat hypo-and dyskinesias of various etiologies. Further investigation of LCGM-10 effects in the delay discounting model of impulsive choice in rats revealed reduced trait impulsivity after single and chronic administrations, suggesting potential implication for attention deficit hyperactivity disorder, obsessive compulsive disorder, and addictions.